Earnings manipulations & related party transactions. Empirical evidence from Italian family firms - Gavana, Giovanna; Gottardo, Pietro; Moisello, Anna Maria (<center>Conference Proceedings Determinants Of Regional Development</center>, 2022)
The literature has extensively investigated the phenomenon of earnings management, as this unethical practice considerably undermines the interests of firms’ stakeholders, in particular of investors, as demonstrated by the financial scandals that have marked the last few decades. The purpose of this paper is to investigate the possible association between earnings management (EM) and related party transactions (RPT). We study a sample of Italian non-financial listed family firms over the 2014–2019 period, controlling for the fixed effects of the company’s industry and the year. We analyze the association between real earnings management (REM), as well as accrual-based earnings management (AEM), and related party transactions in family businesses. In doing so, we distinguish earnings manipulations perpetrated by exploiting accounting choices, as well as production cost, cash flow, and discretionary expenses-based earnings management. We control for certain governance characteristics and family business generational stage, leverage, size and performance in order to take into account the heterogeneity within family firms. We find a significant negative relation between real earnings management perpetrated by overproduction and RPTs, as well as a significant positive relation between abnormal levels of discretionary expenses and RPTs. Moreover, our results indicate that CEO duality significantly increases the association between REM perpetrated via cash flow manipulations and RPTs, whilst firms in the first generational stage tend to use in a substitute way downward accrual-based earnings management and RPTs.